2005
DOI: 10.4018/irmj.2005100101
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Intent and E-Business in SMEs

Abstract: Small firms' use of e-business is limited and little is known about what drives small businesses (SMEs) to embrace e-business. It first discusses different growth strategies adopted by SMEs and reviews Internet adoption in SMEs. Drivers and inhibitors of e-business are identified. Three research questions are derived-does strategic intent drive e-business adoption and is it a factor of market position or product innovation? Is this consistent across sectors? And how is strategic intent and industry adoption in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 35 publications
1
46
0
1
Order By: Relevance
“…In the following sections, we investigate these organisational resources with a particular focus on several select human, business, and external resources pertinent to SMEs. These resources have been widely recognised for their important roles in linking IT/e-commerce with firm performance (Thong 2001;Levy, Powell, and Yetton 2002;Sauer and Willcocks 2002;Levy, Powell, and Worrall 2005;Siqueira and Fleury 2011;Li, Lin, and Huang 2014).…”
Section: An Rbv Model and Hypotheses Related To The It/e-commerce Invmentioning
confidence: 98%
“…In the following sections, we investigate these organisational resources with a particular focus on several select human, business, and external resources pertinent to SMEs. These resources have been widely recognised for their important roles in linking IT/e-commerce with firm performance (Thong 2001;Levy, Powell, and Yetton 2002;Sauer and Willcocks 2002;Levy, Powell, and Worrall 2005;Siqueira and Fleury 2011;Li, Lin, and Huang 2014).…”
Section: An Rbv Model and Hypotheses Related To The It/e-commerce Invmentioning
confidence: 98%
“…2). Previous research (Grandon et.al., 2004, Levy et al, 2005b, Van Akkeren and Cavaye, 1999, Thong and Yap, 1995, Iacovou, 1995, Rashid et al, 2001, Merhten et al, 2001, Storey, 1994 indicated that the presence of in-house skills is imperative in the successful adoption of technology. It would now appear that this also affects the growth in terms of turnover for ICT companies.…”
Section: Perceived Valuementioning
confidence: 99%
“…They also describe the SME market as investing in information systems at start up and then no further development until the business outgrows its first purchase. Levy et al (2005b) claim that many of the drivers can be described as perceived benefits and many of the inhibitors are recognized as being due to management limitations. Grandon and Pearson (2004) analysed ten ICT adoption models to determine the main ICT adoption factors and found that many of the same issues recurred throughout the literature.…”
Section: Edi Ebusiness and Internet Adoption Modelsmentioning
confidence: 99%
“…The profile for those who had progressed beyond Phase I (brochure ware) and had moved into Phase II (transactions) and Phase III (integration) included IT support being provided by either a staff member whose main responsibility is not IT supported (four respondents) or an external contractor (four respondents), ADSL providing the means of Internet access, spending greater than 5% of their budget on IT, the use of EDI, and movement into use of wireless and satellite access to the Internet. (Poon, 1999;Metts, Monge, & Rao, 2003;Mandel & Hof, 2001;Kalakota & Robinson, 2001;Dholakia & Kshetri, 2004), others had proposed that SMEs' greater use of the Internet was achieved caused by characteristics of the entrepreneur and his/her attitude toward growth, the firm, and its context (Levy & Powell;Storey, 1994).…”
Section: Finding 1:1mentioning
confidence: 99%
“…In Canada, for example, SMEs are responsible for 60% of economic output, generate 80% of national employment, and create 85% of all new jobs Shape the future, 2008). However, according to published research, for a variety of reasons, many of which are internal and behavior related, most SMEs have yet to fully embrace e-business capabilities with many limiting their involvement to e-mail and/or brochure ware Web sites (Levy, et al, 2005, Rola, 2002.…”
Section: Smesmentioning
confidence: 99%